2021
DOI: 10.3390/app11041756
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Training and Match-Play External and Internal Load of Elite Gaelic Football Players

Abstract: The current investigation quantified the training and match-play load of elite Gaelic football players across a two-season period using global positioning system technology (GPS), rating of perceived exertion (RPE) and sessional rating of perceived exertion (sRPE). Total weekly workload variables were collected across GPS, RPE, and sRPE across thirty-six elite Gaelic footballers (mean ± SD, age: 26 ± 5 years; height: 177 ± 8 cm; mass: 81 ± 7 kg) from one elite squad during a two-season observational period. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Acceleration and CODS (agility) are of paramount importance to on-field performance, especially in Gaelic games which are high intensity, multi-directional, collision field sports similar to rugby and soccer in terms of physiological demands [27][28][29][30]33]. A previous paper from the current research group demonstrated that acceleration and CODS are reduced in athletes with FAI [35].…”
Section: Discussionmentioning
confidence: 88%
“…Acceleration and CODS (agility) are of paramount importance to on-field performance, especially in Gaelic games which are high intensity, multi-directional, collision field sports similar to rugby and soccer in terms of physiological demands [27][28][29][30]33]. A previous paper from the current research group demonstrated that acceleration and CODS are reduced in athletes with FAI [35].…”
Section: Discussionmentioning
confidence: 88%
“…Gaelic football is one of the national sports of Ireland and can be characterized as a high intensity, intermittent fieldsport [1]. The game is composed of repeated high intensity actions superimposed across periods of lower intensity activities such as walking, jogging, or standing [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Match running performance data helps to inform training practice. This provides coaches with the distances and intensities needed within specific training drills to prepare players to meet the demands of competition [1,14,15]. Previous literature across multiple sports has shown that position has a significant impact on the demands of match-play [5,6,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the periodization practices in professional soccer will be helpful for performance and technical coaches to manipulate the training volume, in order to help players increase their physical levels during different phases of a soccer season [ 30 ]. However, due to the lack of clear evidence in professional players, the periodization practices in soccer are currently poorly known and are reliant on the coach’s training philosophy based on years of coaching experience [ 31 ].…”
Section: Introductionmentioning
confidence: 99%